Debris and sadness. Visual poetry between elegy and irony - Glüher, Gerhard (Scenari, 2024)
The reference objects of the following investigation are artistic photographs that the photographer Alberto Petrò took in the past two years at different locations in Europe. The set of images is titled ‘Metamorphoses’ and is published on his homepage. Especially for the second part of this text, it is recommended to consult the images to better understand the analyses, although the imagined images can also be thought of. In the juxtaposition of this visual research, Marc Augé’s concept of the ‘lost place’ is critically questioned and brought into dialogue with spatial theories by Kracauer, Benjamin, Husserl, Krämer and Canetti. The method of seeing, registering and representing through photography and the perceiving person has the characteristic of the flâneur, who, in a Benjamian sense, seeks out his places and sites and condenses them in open or unclear situations, which are called ‘sites’ in an in-between space. The analysis in the second part of the text focuses on this phenomenon of the fragmentation of space-time. In the sense in which Cassirer uses it, presence and absence are just as intrinsic to the image as the so-called ‘third space’, a term introduced by Homi K. Bhabha. Roland Barthes’s peculiar method of reading the ‘dotted image’ is the basis for the last part of the investigation, which turns to the categories of the provisional, the fragment, the atmosphere, the crack and loneliness. The epilogue refers to Karl Rosenkranz’s writing on the aesthetics of the ugly and attempts to cite the phenomenon of patina as an architectural-aesthetic momentum and argument in order to answer the question of why the vague symbolism of the architectural fragments can only be insufficiently answered. In this sense, the essay is also an attempt to reconstruct what is absent through the intensive study of photographs, and this discourse includes its failure – it is an experiment on the text of what has been seen.